IDENTIFICATION AND PREVALENCE OF ECTOPARASITES IN BLUE SWIMMING CRAB (Portunus pelagicus Linnaeus, 1758) ON THE NORTH COAST OF JAVA: IDENTIFIKASI DAN PREVALENSI EKTOPARASIT PADA RAJUNGAN (Portunus pelagicus Linnaeus, 1758) DI PANTAI UTARA PULAU JAWA - Adela Shofirma; Majariana Krisanti; Nurlisa A. Butet; Ali Mashar (Jurnal Teknologi Perikanan dan Kelautan, 2025)
Besides overfishing, other factors that influence the decline in blue swimming crab (Portunus pelagicus) production are diseases caused by parasites. Poor environmental conditions could trigger parasite infestation on their host. This study aims to identify ectoparasites morphologically based on the research location and to analyze the prevalence of ectoparasites of the blue swimming crabs. Crab samples and data collection of aquatic environmental parameters were carried out at five locations in the northern part of Java Island, Indonesia: Pasuruan, Lamongan, Semarang, Cirebon, and Banten. The study was conducted from December 2021 to July 2023. Morphological identification of ectoparasites was carried out at the Biology Micro Laboratory I, Department of Aquatic Resources Management, IPB University. Interviews with fishermen were also conducted to ensure the crab catchment area around the research location. The number of blue swimming crabs obtained at each location varied, ranging from 25 to 35 individuals, consisting of large, medium, and small crabs. Based on the results of morphological identification, there were a total of five types of parasites found in all research locations, namely Allokepon sp., Chelonibia testudinaria, Octolasmis angulata, Octolasmis warwickii, and Octolasmis sp. The prevalence rate of crabs in each location was significantly different in five locations, namely Pasuruan, Lamongan, Semarang, Cirebon, and Banten, which were 80%, 74%, 80%, 12%, and 70%, respectively. The highest prevalence was in Pasuruan and Semarang. Factors affecting the prevalence rate of ectoparasites in blue swimming crabs included environmental quality such as temperature, salinity, pH, and dissolved oxygen (DO).